Birth order and socioeconomic disadvantage predict behavioural and emotional problems at age 3 years. (8th September 2021) - Hjern, Anders; Bergström, Malin; Fransson, Emma; Lindfors, Anncharlotte; Bergqvist, Kersti
Abstract: Aim: The aim of this study was to describe sociodemographic and family predictors for behavioural and emotional problems in pre‐schoolers. Methods: This was a cross‐sectional study including 30, 795 children in the Stockholm region whose parents had completed the Strength and Difficulties Questionnaire (SDQ) prior to a routine visit to a well‐baby clinic at age 3 years. Multivariate logistic regression was used to analyse predictors for having a high total SDQ difficulties score. Results: Young parental age and a low level of parental education predicted high total SDQ score in a stepwise pattern. Being a first‐born child was associated with a high SDQ score with an adjusted odds ratio of 2.10 (95% C.I. 1.84–2.41), compared with having older siblings. A sole physical custody arrangement predicted a high total SDQ score after parental separation. The percentage of children with a high total SDQ score increased with the Care Need Index (CNI) of the well‐baby clinic. Conclusions: This study identified socioeconomic disadvantage and being the first‐born child as the main predictors of poor mental health at age 3 years. Well‐baby clinics with socioeconomically disadvantaged catchment areas should be provided with adequate resources and methods for equitable prevention.